A factor from Actinomyces viscosus T14V that specifically aggregates Streptococcus sanguis H1. - Mizuno, J (1983)
A highly specific aggregation factor for Streptococcus sanguis H1 (AFH1) was obtained by lysozyme treatment of Actinomyces viscosus T14V. At 1 micrograms/ml, AFH1 aggregated a suspension of S. sanguis H1, with which A. viscosus T14V coaggregates by a mechanism not inhibited by lactose: even at much higher levels AFH1 caused little or no aggregation of streptococci from other coaggregation groups (J. O. Cisar et al., Infect. Immun. 24:742-752, 1979). The most active fraction of AFH1 obtained by gel chromatography (near the void volume of Bio-Gel A1.5 m) reacted as a single antigen with anti-A. viscosus T14V serum and was unrelated to the fimbrial antigens of A. viscosus T14V. Smaller molecular fractions, at high levels, inhibited aggregation of S. sanguis H1 by high-molecular-weight AFH1 as well as coaggregation of S. sanguis H1 with A. viscosus T14V. The AFH1 fraction with high aggregating activity was composed of approximately 53% cell wall components (alanine, glutamine, lysine, N-acetylglucosamine, and N-acetylmuramic acid). 40% polysaccharide (N-acetylgalactosamine, rhamnose, and 6-deoxytalose), and 7% protein; teichoic acid was not detected. The fraction which inhibited aggregation and coaggregation contained much less of the cell wall constituents and more of the polysaccharide than the fraction with potent aggregating activity. Aggregation was completely prevented either by treating AFH1 with 0.01 M periodate at 25 degrees C for 4 h or by treating S. sanguis H1 with heat or pronase. A role for electrostatic forces in the aggregation was indicated by: (i) NaCl inhibition of aggregation, and (ii) a great decrease in aggregation potency as a result of chemical modification of either cationic or anionic groups of AFH1. On the other hand, NaCl reversed the aggregation only very weakly. The overall data suggest that a carbohydrate-protein interaction may be dominant in the aggregation of S. sanguis H1 by AFH1 and in the coaggregation of S. sanguis H1 with A. viscosus T14V.